2020
DOI: 10.1177/1046878120958750
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Leadership in Collegiate Esports

Abstract: Background. Current research supports the use of recreational games in higher education settings for student development. Team-based esports in collegiate settings offer leadership experiences analogous to other organizational contexts. Distributed leadership reflects leader roles shared dynamically with multiple points of salience and dynamic or absent hierarchy. Aim. This study looked at elements of distributed leadership claimed among collegiate esports teams and whether esports play contributed to distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Out of 18 qualitative studies, only four studies [18,32,52,88] met all the criteria, whereas 14 qualitative studies offered limited descriptions of research methods that rendered the connection between the presented data and conclusions implicit. Five of these studies [45,53,64,111] failed to meet any of the criteria assigned to the qualitative category.…”
Section: Rq3: To What Extent Did Such Research Meet the Established Q...mentioning
confidence: 99%
See 3 more Smart Citations
“…Out of 18 qualitative studies, only four studies [18,32,52,88] met all the criteria, whereas 14 qualitative studies offered limited descriptions of research methods that rendered the connection between the presented data and conclusions implicit. Five of these studies [45,53,64,111] failed to meet any of the criteria assigned to the qualitative category.…”
Section: Rq3: To What Extent Did Such Research Meet the Established Q...mentioning
confidence: 99%
“…However, these studies, like those in the heroic category, remain silent on issues of asymmetries of power, privilege, and ways of handling these differences. Out of 36 studies only three were in this category [30,52,53]. Whilst considering leadership at a classroom [30] and institutional [53] as well as higher education students esports games level [52] in relation to teaching and programme delivery levels, these researchers acknowledge the wider network of relationships and mutual influences within which leadership of key actors is taking place.…”
Section: Post-heroic Digital Leadership Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, Himmelstein et al ( 2021) found esports competitors with poor communication and team dynamics struggled to achieve optimal performance within the game suggesting that the ability to work with others is critical. Additionally, participants have articulated how the information-heavy nature of the games requires players to constantly partake in individual and group level decision-making, leading to a form of distributed leadership where the role of leader is dynamically passed between players depending on the situational context (Falkenthal & Byrne, 2020). Further, Tauer and Harackiewicz (2004) and Cagiltay et al (2015) found spaces such as course-based games that combine intra-and inter-team collaboration and competition result in heightened motivation and performance as well as increased engagement in the activity and overall learning.…”
Section: Esports / Multiplayer Online Battle Arenasmentioning
confidence: 99%